Usefulness of Preoperative Simulation in Skull Base Approach: A Case Report - Kolakshyapati, Manish; Ikawa, Fusao; Abiko, Masaru; Mitsuhara, Takafumi; Takeda, Masaaki; Shrestha, Tejashwi; Kurisu, Kaoru (Journal of Neurological Surgery Part B: Skull Base, 2018)
Skull base approach is a neurosurgical challenge requiring dexterity of the operating surgeon for good postoperative outcome. In addition to the experience of the operating surgeon, adequate preoperative information of the tumor is necessary to ensure better outcome. In clinoid meningioma, it is sometimes difficult to determine its relationship with the surrounding structure and the feeding artery. Previously, preoperative simulation has been utilized to determine the intracranial course of the compressed nerves in relation to the petroclival meningioma. We report a case of clinoid meningioma where preoperative fusion of three dimensional computed tomography angiography (3D-CTA) and 3T-fast imaging employing steady-state acquisition (FIESTA) images was useful in determining the exact location of the feeding artery to devascularize the tumor and aid in surgery. Preoperative simulation with three-dimensional digital subtraction angiography (3D-DSA) and 3T-FIESTA fusion images can be a useful adjunct tool to supplement surgery and to train neurosurgical trainees.
Keywords: preoperative simulation; skull base; 3D-CTA; FIESTA; clinoid meningioma; feeding artery